2019
DOI: 10.1029/2018gl080544
|View full text |Cite
|
Sign up to set email alerts
|

Efficient In‐Cloud Removal of Aerosols by Deep Convection

Abstract: Convective systems dominate the vertical transport of aerosols and trace gases. The most recent in situ aerosol measurements presented here show that the concentrations of primary aerosols including sea salt and black carbon drop by factors of 10 to 10,000 from the surface to the upper troposphere. In this study we show that the default convective transport scheme in the National Science Foundation/Department of Energy Community Earth System Model results in a high bias of 10–1,000 times the measured aerosol m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
94
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(105 citation statements)
references
References 44 publications
9
94
2
Order By: Relevance
“…Additional future improvements for the model are planned to include the addition of the optical properties and radiative effects of brown carbon (Brown et al, ) and updates in below cloud top scavenging. These will likely improve the high bias of BC (and POM) in middle to upper troposphere as pointed out by Yu et al (), who used the same model code for cloud top scavenging. Both these updates are expected to further impact radiative effects in CESM2.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Additional future improvements for the model are planned to include the addition of the optical properties and radiative effects of brown carbon (Brown et al, ) and updates in below cloud top scavenging. These will likely improve the high bias of BC (and POM) in middle to upper troposphere as pointed out by Yu et al (), who used the same model code for cloud top scavenging. Both these updates are expected to further impact radiative effects in CESM2.…”
Section: Discussionmentioning
confidence: 85%
“…WACCM6‐VBSext shows a slight improvement in the high bias, and a significant improvement in BC in the Arctic lower troposphere (Figures and ). Yu et al () have shown that wet scavenging above the cloud top in all CESM2 configurations is largely underestimated, which results in the high bias. On the other hand, WACCM6‐VBSext shows much more realistic BC values in the lower troposphere (below 5 km) compared to WACCM6‐SOAG.…”
Section: Aerosol Burden and Radiative Forcings For Different Cesm2 Comentioning
confidence: 99%
“…Aerosol wet scavenging considers incloud scavenging (the removal of cloud-borne particles that were activated at the cloud base) and below-cloud scavenging for both convective and grid-scale clouds. CESM1-CARMA simulations use the configuration described in Yu et al (2019) which is based on CESM1 and the sectional Community Aerosol and Radiation Model for Atmospheres (CARMA v3.0). Anthropogenic emissions are those from the Greenhouse gas-Air pollution Interactions and Synergies (GAINS) model, and biomass burning emissions are from the Global Fire Emission Database (GFED v3, van der Werf et al, 2010).…”
Section: Gc10-tomas Is Based On the Geos-chem Version 1001 Coupled Wmentioning
confidence: 99%
“…The removal of OA occurs only by dry and wet deposition. Compared to the CESM2-SMP and CESM2-DYN simulations, the convective removal of aerosols uses the modified scheme described in Yu et al (2019) which accounts for aerosol secondary activation from the entrained air above the cloud base, and the scavenging of activated aerosols in convective updrafts. The default CESM can transport aerosols from the cloud base to the top of the cloud in strong convective updrafts in one time step without scavenging them, while the new scheme allows for a more efficient removal off all aerosols inside convective clouds.…”
Section: Gc10-tomas Is Based On the Geos-chem Version 1001 Coupled Wmentioning
confidence: 99%
“…The overestimation of the BC 20 lifetime may be attributed to the overestimation of the convective mass flux above 500 hPa, which may be improved by increasing the number of vertical layers in the model (Allen and Landuyt, 2014). Another possibility is a lack of secondary aerosol activation by convective clouds and associated removal by precipitation (Yu et al, 2019).…”
Section: By Comparing Aerosolmentioning
confidence: 99%